Navigating the Geopolitical Tightrope: The Complex Dynamics of Sino-EU Relations in a Shifting World Order - Rahman Nurdun (Ankara Avrupa Çalışmaları Dergisi)
In recent years, a discernible shift has occurred in the European Union's (EU) stance and policies towards China, prompted by a confluence of crises including different interpretation of human rights concept, the conflict between Ukraine and Russia as well as Sino-US tensions. Meanwhile, many European Union (EU) countries express skepticism about China's Belt and Road Initiative (the BRI), perceiving it as a potential threat to their national interests. In the event of a confrontation between the US and China, the EU is gradually inclined to align itself with the US. Despite its economic prowess, the EU, as a collective entity, is viewed as strategically limited when dealing with China, resorting mainly to technology and commercial restrictions. The EU finds itself walking a delicate line, leveraging its economic strength yet recognizing its strategic constraints in addressing the multifaceted relationship with China. In light of these developments, this article seeks to analyze the evolving dynamics of Sino-EU relations, leading to an inherently unstable partnership.